BMSC-derived extracellular matrix better optimizes the microenvironment to support nerve regeneration. (January 2022) - Wang, Shengran; Zhu, Changlai; Zhang, Bin; Hu, Junxia; Xu, Jinghui; Xue, Chengbin; Bao, Shuangxi; Gu, Xiaokun; Ding, Fei; Yang, Yumin; Gu, Xiaosong; Gu, Yun
Abstract: A favorable microenvironment plays an important role in nerve regeneration. Extracellular matrix (ECM) derived from cultured cells or natural tissues can facilitate nerve regeneration in the presence of various microenvironmental cues, including biochemical, spatial, and biomechanical factors. This study, through proteomics and three-dimensional image analysis, determines that the components and spatial organization of the ECM secreted by bone marrow mesenchymal cells (BMSCs) are more similar to acellular nerves than those of the ECMs derived from Schwann cells (SCs), skin-derived precursor Schwann cells (SKP–SCs), or fibroblasts (FBs). ECM-modified nerve grafts (ECM-NGs) are engineered by co-cultivating BMSCs, SCs, FBs, SKP-SCs with well-designed nerve grafts used to bridge nerve defects. BMSC-ECM-NGs exhibit the most promising nerve repair properties based on the histology, neurophysiology, and behavioral analyses. The regeneration microenvironment formed by the ECM-NGs is also characterized by proteomics, and the advantages of BMSC-ECM-NGs are evidenced by the enhanced expression of factors related to neural regeneration and reduced immune response. Together, these findings indicate that BMSC-derived ECMs create a more superior microenvironment for nerve regeneration than that by the other ECMs and may, therefore, represent a potential alternative for the clinical repair of peripheral nerve defects.